2023
DOI: 10.1021/acs.chemmater.3c01120
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Perspective of the Crystallization of Naphthodithiophene in Two Hydrocarbon Solvents

Chamikara Karunasena,
Zoran Bjelobrk,
Chad Risko

Abstract: A priori control over crystallization, whether one attempts to induce or prevent crystallization, is critical across many areas of materials chemistry. The capacity to regulate crystallization in solution requires a comprehensive understanding of the deceivingly simple interrelationships among the chemical compositions and structures of the solute and solvent and external environmental parameters such as temperature and pressure. While there have been tremendous advances in crystal structure prediction based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Exerting precise control over the crystallization process is critical in improving material quality and performance, yet often being a formidable challenge. [1][2][3][4][5][6] It has been observed that crystallization via particle attachment is prevalent across various materials, rendering the classical nucleation and growth theory inapplicable. [7][8][9][10][11] An example is the two-dimensional covalent organic frameworks (2D COFs), which have attracted significant attention in recent years owing to their promising applications in catalysis, [12][13][14][15][16] optoelectronics, [17][18][19][20][21][22][23] energy storage devices, [24][25][26][27][28] and molecular separation [29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…Exerting precise control over the crystallization process is critical in improving material quality and performance, yet often being a formidable challenge. [1][2][3][4][5][6] It has been observed that crystallization via particle attachment is prevalent across various materials, rendering the classical nucleation and growth theory inapplicable. [7][8][9][10][11] An example is the two-dimensional covalent organic frameworks (2D COFs), which have attracted significant attention in recent years owing to their promising applications in catalysis, [12][13][14][15][16] optoelectronics, [17][18][19][20][21][22][23] energy storage devices, [24][25][26][27][28] and molecular separation [29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…Exerting precise control over the crystallization process is critical in improving material quality and performance, yet often being a formidable challenge. [1][2][3][4][5][6] It has been observed that crystallization via particle attachment is prevalent across various materials, rendering the classical nucleation and growth theory inapplicable. [7][8][9][10][11] An example is the two-dimensional covalent organic frameworks (2D COFs), which have attracted significant attention in recent years owing to their promising applications in catalysis, [12][13][14][15][16] optoelectronics, [17][18][19][20][21][22][23] energy storage devices, [24][25][26][27][28] and molecular separation.…”
Section: Introductionmentioning
confidence: 99%